Essential mathematics for convex optimization - Kılınç-Karzan, Fatma; Nemirovskiĭ, A. S. (Arkadiĭ Semenovich) (Cambridge University Press, 2026)
With an emphasis on timeless essential mathematical background for optimization, this textbook provides a comprehensive and accessible introduction to convex optimization for students in applied mathematics, computer science, and engineering. Authored by two influential researchers, the book covers both convex analysis basics and modern topics such as conic programming, conic representations of convex sets, and cone-constrained convex problems, providing readers with a solid, up-to-date understanding of the field. By excluding modeling and algorithms, the authors are able to discuss the theoretical aspects in greater depth. Over 170 in-depth exercises provide hands-on experience with the theory, while more than 30 'Facts' and their accompanying proofs enhance approachability. Instructors will appreciate the appendices that cover all necessary background and the instructors-only solutions manual provided online. By the end of the book, readers will be well equipped to engage with state-of-the-art developments in optimization and its applications in decision-making and engineering.
Title from publisher's bibliographic system (viewed on 28 Oct 2025).
Keywords: Mathematical optimization -- Textbooks.; Convex programming -- Textbooks.; Convex sets -- Textbooks.